Management of dyslipidemia and hyperglycemia with a fixed-dose combination of sitagliptin and simvastatin - Steinberg, Helmut (Dove Medical Press, 2013)
The risk of death due to heart disease and stroke is up to four times higher in individuals with diabetes compared to individuals without diabetes. Most guidelines that address treatment of dyslipidemia in patients with diabetes consider diabetes a cardiovascular disease (CVD) “risk equivalent” and recommend intensive treatment of dyslipidemia for the purpose of CVD prevention. Statins (3-hydroxy 3-methylglutaryl coenzyme A reductase [HMG-CoA reductase] inhibitors) are first-line agents in achieving lipid goals as an adjunct to diet and exercise and should be used in most patients. In addition to lipid management and blood pressure control, glycemic control is a basic component in the management of diabetes. Glycemic control is achieved by combining diabetes self-management education, diet and exercise, and, where required, antihyperglycemic agents (OHAs). Persistence and adherence to therapy are critical in achieving recommended treatment goals. However, overall compliance with concomitantly prescribed OHAs and statins is low in patients with type 2 diabetes. Fixed-dose combination (FDC) therapies have been shown to improve adherence by reducing pill burden, the complexity of treatment regimen, and, potentially, cost. Based on the available evidence regarding the pharmacokinetics and the efficacy and safety profiles of each component drug, the sitagliptin/simvastatin FDC may provide a rational and well-tolerated approach to achieving better adherence to multiple-drug therapy and improved lipid lowering and glycemic control, with consequent reduction in cardiovascular risk, diabetic microvascular disease, and mortality in diabetic patients for whom treatment with both compounds is appropriate.